2019
DOI: 10.1016/j.envpol.2018.11.097
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants in Atlantic walruses in Svalbard Part 2: Relationships with endocrine and immune systems

Abstract: Marine mammals in the Barents Sea region have among the highest levels of contaminants recorded in the Arctic and the Atlantic walrus (Odobenus rosmarus rosmarus) is one of the most contaminated species within this region. We therefore investigated the relationships bewteen blubber concentrations of lipophilic persistent organic pollutants (POPs) and plasma concentrations of perfluoroalkyl substances (PFASs) and markers of endocrine and immune functions in adult male Atlantic walruses (n=38) from Svalbard, Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…Discussing the effects of contaminants on health status is beyond the scope of this review; however, contaminants should be considered in the context of consequences of multiple stressors on individual populations with documented deleterious additive effects in relation to population health status [ 19 , 410 , 411 ]. Recent publications exploring the immune status of walruses in Svalbard and the effects of contaminants on their health status demonstrate the complex interplay of factors and the need for directed scientific study to answer the question regarding the impact of climate change impact health [ 412 , 413 ]. Similarly, it is well documented that the poor health observed in the St Lawrence white whale population was primarily due to contaminants in this area some decades ago, and that when the environment was improved, white whale health also improved [ 379 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discussing the effects of contaminants on health status is beyond the scope of this review; however, contaminants should be considered in the context of consequences of multiple stressors on individual populations with documented deleterious additive effects in relation to population health status [ 19 , 410 , 411 ]. Recent publications exploring the immune status of walruses in Svalbard and the effects of contaminants on their health status demonstrate the complex interplay of factors and the need for directed scientific study to answer the question regarding the impact of climate change impact health [ 412 , 413 ]. Similarly, it is well documented that the poor health observed in the St Lawrence white whale population was primarily due to contaminants in this area some decades ago, and that when the environment was improved, white whale health also improved [ 379 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between PFASs and the status of different immunologic parameters or apparent immunologic function have also been investigated in other marine mammals such as walruses (Odobenus rosmarus) by Routti et al (2019) and sea otters (Enhydra lutris) by Kannan et al (2006). In the study with Atlantic walruses from Svalbard the main findings were: 1) a positive correlation of lipophilic POPs in blubber with thyroxine (TT4) concentrations and the TT4 and reverse triiodothyronine ratio and 2) a decreased blood cell transcript levels of genes involved in the function of T and B cells (Routti et al, 2019). The findings of the sea otter study revealed sex-, seasonal-and time-trends with a clear association between infectious diseases occurrence and elevated concentrations of PFOS and PFOA (Kannan et al, 2006).…”
Section: Other Marine Vertebrates: Turtles Seabirds and Mammalsmentioning
confidence: 99%
“…The qRT-PCR assays were carried out in 96-well reaction plates with an iCycler iQ5 (Bio-Rad Laboratories, Hercules, CA, United States) using the SsoAdvanced Universal SYBR Green Supermix (Bio-Rad Laboratories, Hercules, CA, United States) as described in Routti et al (2019).…”
Section: Rna Isolation and Quantitative Real-time Pcr Analysismentioning
confidence: 99%